Potkamenica Cove shipwreck, island of Šolta, Croatia - Kaleb, Maja (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The remains of a shipwreck located in the Potkamenica Cove on the island of Šolta were researched, documented and protected in situ in 2020, one decade after its discovery. The shipwreck is gravely devastated due to uncontrolled anchoring, but parts of the keel and one side of the ship with its belonging elements, planks and futtocks are partially preserved. The ship was built using the shell-first technique using the distinctive assembly method of tenon-and-mortise joinery. The sinking of the ship was dated in the 4th century by using the 14C AMS method and by the comparative analysis of movable archaeological material.